Examining Ki Hajar Dewantara's Educational Democracy in the Contemporary Classroom - Ardiansyah, Zidane; Hendriwanto, Hendriwanto (JENTRE, 2025)
This study aims to explore how a teacher interprets and applies Ki Hajar Dewantara's educational democracy in contemporary classrooms. The research employs a qualitative method with a single case study design, where data were collected through open-ended interviews and observations of a teacher applying democratic principles in their classroom. The data were processed using thematic analysis with descriptive coding. The findings reveal four main themes: (1) Democratic Values in Education through Ki Hajar Dewantara’s Philosophy, (2) Educational Democracy within the Framework of the Trilogi Kepemimpinan, (3) Innovation in Democratic Education, and (4) The Challenges of Democracy in Contemporary Classrooms. The findings indicate that the instructor sees Dewantara's democratic values as responsible freedom for children to voice their views and equal rights regardless of background. This is accomplished through the Leadership Trilogy, which positions the teacher as a role model, replaces punishment with class agreements, and promotes a good classroom climate. To challenge neoliberalism and neoconservatism in education, the teacher employs democratic concepts such as local methods, experiential learning, and the integration of spiritual dimensions. The obstacles experienced by teachers in implementing educational democracy are related to the ever-changing "kodrat alam" and "kodrat zaman" of pupils, as well as varying perspectives among Tripusat Pendidikan members. However, these difficulties are overcome through reflection and self-improvement.